From EU governance of crisis to crisis of EU governance: regulatory failure, redistributive conflict, and Euroskeptic publics - Börzel, Tanja A. (2016)
Abstract: This paper takes issue with the widely held view that Europe has failed to govern the multiple crises it has been facing because of too little integration. Rather than a lack of authority, a growing “commitment-compliance gap” has exacerbated the regulatory deficits of EU governance in core areas of the European integration project. The failure of the Member States to put into practice the policies they agreed upon at the EU level has its cause in Euro-nationalists dominating the politicization of EU policies and institutions. They have been empowered by the way in which the Member States have sought to solve the Euro crisis. The growing contestation of and opposition to the EU and its policies per se is not the problem. Nor is it the return of nationalism in Europe or the lack of a European public sphere. Instead of an outright rejection of European integration, we see the mobilization of illiberal, nationalist ideas of Europe, which are exclusionary, xenophobic, and anti-Islam. T